Clinical characteristics of 662 patients with pancreatic neuroendocrine tumors receiving antitumoral therapy. Issue 50 (16th December 2022) - Loosen, Sven H.; Kostev, Karel; Eschrich, Johannes; Krieg, Sarah; Krieg, Andreas; Luedde, Tom; Jann, Henning; Roderburg, Christoph
Abstract : Pancreatic neuroendocrine neoplasia constitute an important subentity of the gastroenteropancreatic neuroendocrine neoplasms accounting for up to 15% of all neuroendocrine neoplasm. Prognosis and oncological behavior of pancreatic neuroendocrine tumors (pNETs) is extremely heterogenous and dependent on the specific tumor stage and differentiation. However, systematic data on the specific epidemiology of pNET are scarce. We identified 662 patients with pNET within the Oncology Dynamics database (IQVIA). Patients were derived from 4 European countries (Germany, France, UK, Spain), 3 Asian countries (Japan, China, South Korea) and 2 South American countries (Mexico and Brazil) and with regard to major patient and tumor related characteristics including patients' age, sex, tumor stage, tumor grading, and differentiation. The mean age of the study cohort was 62 years (SD 12 years) with 53.9.1% of all patients being male. The majority of patients had an Eastern co-operative of Oncology Group 1 performance status (63.3%). The most common Union international contre le cancer tumor stage was stage IV (85%) with liver metastases (89.0%) representing the most common site of extra-pancreatic tumor manifestation. The majority of all patients displayed well or moderate tumor differentiation (9.6% of patients had a Ki-67 expression below 2%. 67.6% of pNET patients had a Ki-67 expression between 2 and 20% and 22.8% of patients showed an expression above 20%). At time point of diagnoses, 93.1% of patients were classified as inoperable. Of note, 93.9 % of patients received systemic anti-tumoral therapy in palliative intention, while treatment was administered in 1.4 % of cases in neoadjuvant and in 4.7% of cases in in an adjuvant setting. Biological therapy was applied to 39.4% of patients, followed by targeted therapies (31.4%) and chemotherapy. Pancreatic neuroendocrine neoplasia are diagnosed in advanced tumor stages, globally. Systemic treatment was the most commonly used treatment modality. Such data may help to better understand the specific epidemiology of pNET worldwide.